The INVENTARISASI JENIS AVES DI KAWASAN TAMAN NASIONAL UJUNG KULON - Ayu Rizqi Maulidah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
This study aims to determine the inventory of aves species in the Ujung Kulon National Park area. The methods used is ecounter rates (meeting rate) and the IPA (Indices Puntuels d'Abondence) or Point Count method. This research was conducted from May to June. Data collection in the form of photos/images is carried out twice a day, in the morning at 06.00 - 11.00 AM and in the afternoon at 15.00 - 18.00 PM. The observations were made at four stations with different ecosystem type: station 1 is Handeleum Island with ecosystem type of coastal and mud forest, station 2 is Cigenteur with vegetation type of mangrove forest, station 3 is Peucang Island with ecosystem type of tropical rain forest and Station 4 is Cidaon with ecosystem type of pasture. Based on observations from the four stations, it found 20 species of aves. Station 1 with amount eight aves species, station 2 with amount of five aves species, station 3 with amount of eleven aves species and station 4 with amount of seven aves species. Particularly, in the stations 1 and 3, more aves were found because coastal water habitats, mud forests and tropical rain forests are habitats that support the availability of abundant food sources also there were many types of trees that serve as shelter and inhabitation. The aves will be in a habitat that has abundant resources to support their needs. Therefore, it can be said that a high level of aves inventory in an area indicates that the area has good environmental conditions.